Aspects of puppet theatre - Jurkowski, Henryk; Francis, Penny (Basingstoke : Palgrave Macmillan, 2013)
Henryk Jurkowski's seminal 1988 text, Aspects of Puppet Theatre, was ground-breaking in its analysis of puppetry as an important performing art. Focusing on the cultural and social functions of puppetry, Jurkowski traced the role of puppetry in cultural life, from its ritualistic roots to its influence on modernist art and presence in contemporary theatre. This new edition of a classic Brings the original text back to life, including four additional essays and a new introduction, edited and translated by leading puppetry scholar Penny Francis. Book jacket
Includes bibliographical references and index
Keywords: Puppet theater